The impact of dietary energy intake on cognitive aging - Mattson, Mark P. (Frontiers in Aging Neuroscience, 2010)
Rodents that are insulin resistant and obese as the result of genetic factors, overeating and/or a sedentary lifestyle, exhibit cognitive deficits that worsen with advancing age compared to their more svelte counterparts. Data from epidemiological and clinical studies suggest similar adverse effects of excessive dietary energy intake and insulin resistance on cognition in humans. Our findings from studies of animal models suggest that dietary energy restriction can enhance neural plasticity and reduce the vulnerability of the brain to age-related dysfunction and disease. Dietary energy restriction may exert beneficial effects on the brain by engaging adaptive cellular stress response pathways resulting in the up-regulation of genes that encode proteins that promote neural plasticity and cell survival (e.g., neurotrophic factors, protein chaperones and redox enzymes). Two energy state-sensitive factors that are proving particularly important in regulating energy balance and improving/preserving cognitive function are brain-derived neurotrophic factor and glucagon-like peptide 1. Alternate day calorie restriction, novel insulin-sensitizing and neuroprotective agents, and drugs that activate adaptive stress response pathways, are examples of approaches for preserving cognitive function that show promise in preclinical studies.